Lithium isotopes differentially modify mitochondrial amorphous calcium phosphate cluster size distribution and calcium capacity - Deline, Marshall L.; Straub, Joshua; Patel, Manisha; Subba, Pratigya; Grashei, Martin; van Heijster, Frits H. A.; Pirkwieser, Philip; Somoza, Veronika; Livingstone, James D.; Beazely, Michael; Kendall, Brian; Gingras, Michel J. P.; et al. (Frontiers in Physiology, 2023)
Lithium is commonly prescribed as a mood stabilizer in a variety of mental health conditions, yet its molecular mode of action is incompletely understood. Many cellular events associated with lithium This is a provisional file, not the final typeset article appear tied to mitochondrial function. Further, recent evidence suggests that lithium bioactivities are isotope specific. Here we focus on lithium effects related to mitochondrial calcium handling. Lithium protected against calcium-induced permeability transition and decreased the calcium capacity of liver mitochondria at a clinically relevant concentration. In contrast, brain mitochondrial calcium capacity was increased by lithium. Surprisingly, 7 Li acted more potently than 6 Li on calcium capacity, yet 6 Li was more effective at delaying permeability transition. The size distribution of amorphous calcium phosphate colloids formed in vitro was differentially affected by lithium isotopes, providing a mechanistic basis for the observed isotope specific effects on mitochondrial calcium handling. This work highlights a need to better understand how mitochondrial calcium stores are structurally regulated and provides key considerations for future formulations of lithium-based therapeutics. 1 2.22.3 Mitochondrial calcium accumulation calcium accumulation and efflux assays